Multifunctional and high-plasticity degradable Zn-Mn-Ga zinc alloy and preparation method thereof
Through the bottom-cycle liquid-cooled casting and deformation heat treatment process of Zn-Mn-Ga zinc alloy, submicron second-phase particles are formed, which solves the inflammation and infection problems of degradable zinc alloys during implantation, achieves high plasticity and strength improvement, and meets the requirements of biocompatibility and antibacterial properties.
Patent Information
- Application Number
- CN202510744433.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-05
- Publication Date
- 2025-09-05
AI Technical Summary
Existing medical non-degradable inert alloy implants require a second surgery to remove after their service life expires, causing physical pain and financial burden to patients. In addition, degradable zinc alloys are prone to cause inflammation, thrombosis, and implant infection during implantation.
Using Zn-Mn-Ga zinc alloy, submicron-sized Ga2MnZn7, GaMnZn8 and (Ga,Mn)Zn9 second phase particles are formed through bottom-cycle liquid cooling casting and deformation heat treatment process, which improves the alloy's antibacterial, anti-inflammatory and plasticity, promotes endothelial cell proliferation and inhibits smooth muscle hyperplasia.
It significantly improves the plasticity and strength of the alloy, degradation uniformity, reduces cytotoxicity, promotes collagen deposition at the wound site, achieves high biocompatibility and antibacterial effect, and reduces the cytotoxicity of alloy element metabolites.
Smart Images

Figure BDA0005435587780000031 
Figure BDA0005435587780000121 
Figure BDA0005435587780000131
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of design and preparation of medical degradable metal material components, and specifically provides a multifunctional, highly plastic degradable Zn-Mn-Ga zinc alloy and a preparation method thereof, which are used in degradable medical implants. Background Art
[0002] Metals, inorganic non-metallic materials, polymers, composite materials, and biomimetic materials are currently used in clinical biomedical applications. Among these, inert medical materials are widely used due to their excellent mechanical and processing properties. Examples include permanent implants such as 316L stainless steel, Ti-6Al-4V titanium alloy, and Co-Cr-Mo cobalt alloy. Implants made from these non-degradable, inert medical alloys require secondary surgery to remove after their lifespan in the human body, adding unnecessary physical pain and financial burden to patients. Therefore, research on biodegradable metal materials, primarily Mg, Zn, and Fe, has gradually become a hot topic in medical materials research.
[0003] Zinc (Zn) is an essential trace element for the human body. Degradable Zn metal, with a degradation rate that matches the recovery rate of human tissue (Zn's standard electrode potential is 0.763V, between that of Mg and Fe), meets the requirements of orthopedics and coronary implants. After performing its function, it gradually degrades, avoiding the risks of secondary surgery or long-term implant retention associated with traditional materials. Therefore, zinc-based materials have become a new generation of biodegradable metal materials for medical applications.
[0004] Pure zinc has low hardness and strength, and poor wear resistance. At room temperature, pure zinc has a hardness of 32 HV, a yield strength of 17 MPa, a tensile strength of 30 MPa, and an elongation of 2% (see Reference 1). Pure zinc is difficult to use in the manufacture of load-bearing medical implants, such as coronary stents and bone screws. Furthermore, a common problem with cast pure zinc and zinc alloys is their extreme brittleness, with room-temperature elongation typically exceeding 3%, severely limiting their application. Using alloying technology, the addition of nutritional elements such as Mg, Fe, and Ca to pure Zn can refine the Zn grain size and improve the alloy's mechanical properties through solid solution strengthening and the formation of second-phase particles.
[0005] Prior art literature: Liu Z, Li R, Jiang R, et al. Effects of Al addition on the structure and mechanical properties of Zn alloys. Journal of Alloys and Compounds. 2016; 687: 885-892. Following existing design concepts, it is feasible to improve the strength of zinc alloys through alloying. However, implanting zinc alloy vascular stents into the human body can easily lead to the following problems:
[0006] (1) The trauma caused by the implantation surgery will destroy the redox homeostasis in the cells, causing inflammatory cells to be activated and release reactive oxygen species (ROS). ROS continue to accumulate in these injured tissues, eventually inducing severe inflammation and pathological reactions.
[0007] (2) Due to the delayed migration and proliferation of endothelial cells and the prolonged exposure of metal to the bloodstream, the risk of late stent thrombosis increases. Excessive proliferation and migration of smooth muscle cells can cause restenosis of blood vessels, disrupt normal hemodynamic balance, promote the formation and development of atherosclerosis, and lead to insufficient blood supply to organs.
[0008] (3) Implant infection caused by Gram-positive bacteria (such as enterococci, Staphylococcus aureus and coagulase-negative Staphylococci) during stent intervention surgery is a common complication.
[0009] Therefore, the development of a medical biodegradable zinc alloy that has anti-inflammatory response, excellent antibacterial properties, selective promotion of endothelial cell proliferation, inhibition of smooth muscle hyperplasia, and high plasticity is a key issue that needs to be urgently addressed. Summary of the Invention
[0010] The present invention aims to provide a multifunctional, highly plastic, biodegradable Zn-Mn-Ga alloy and its preparation method, addressing the persistent accumulation of ROS in injured tissues, which can lead to severe inflammation and pathological reactions, organ blood supply insufficiency, and implant infection. The alloy combines high functionality (i.e., high anti-inflammatory properties, excellent antibacterial properties, selective promotion of endothelial cell proliferation, and inhibition of smooth muscle hyperplasia) with high plasticity.
[0011] The basis for selecting alloying elements in the present invention is as follows:
[0012] Manganese (Mn), as an essential trace metal element for the human body, is a key cofactor of multiple enzymes (such as manganese superoxide dismutase and pyruvate carboxylase). It participates in physiological processes such as antioxidant defense, energy metabolism, bone development, and neurotransmitter regulation. It can reduce cardiovascular oxidative damage and support vascular collagen synthesis. It enhances antiviral ability by activating immune pathways (such as cGAS-STING) and affects reproductive hormone synthesis.
[0013] Gallium (Ga) is a bone-strengthening and calcium-solidifying agent in the human body. It can be used to treat cancer-related hypercalcemia and osteitis deformans, and has a certain therapeutic effect on bladder cancer and non-Hodgkin's lymphoma. 3+ It can inhibit osteoclast resorption, inhibit bone dissolution, prevent the release of bone calcium, change the gene expression of type I collagen and fibrin in the bone, which is conducive to the formation of new bone. It can also increase the content of calcium and phosphorus in the bone, and directly act on the formation of human bone; Ga 3+ It has excellent antibacterial properties, can block the bacteria's access to nutrients, and destroy the bacteria's Fe metabolism; Ga 3+ It promotes the polarization of macrophages to the M2 anti-inflammatory and repair type, and has anti-inflammatory effects.
[0014] Therefore, a new medical degradable Zn-Mn-Ga zinc alloy was designed. Currently, there are no literature or patents reporting biodegradable Zn-Mn-Ga alloys and their preparation methods at home and abroad.
[0015] The Zn-Mn-Ga zinc alloy has the following four characteristics:
[0016] (1) The composition is calculated as a percentage by weight of the total weight, wherein the zinc content is 60 to 99.98 wt.%, preferably the manganese content is 0.01 to 20 wt.%, preferably the gallium content is 0.01 to 20 wt.%, and the remainder is other alloying elements artificially added;
[0017] (2) Zn 2+ Release rate ≥1.0mg / (cm 2 ·day), Mn 2+ Release rate ≥0.05mg / (cm 2 ·day), Ga 3+ Release rate ≥0.1mg / (cm 2 day), the cytotoxicity of alloy element metabolic ions was level 0, the antibacterial rate was ≥85%, and the increase in anti-inflammatory factors (such as interleukin-4 release) in rats was ≥100%, and the collagen deposition efficiency in the wound was increased by ≥50%;
[0018] (3) Yield strength ≥ 250 MPa, tensile strength ≥ 280 MPa, hardness ≥ 65 HV, tensile strength ≥ 580 MPa, elongation ≥ 90%, stress concentration factor ≤ 1.6, strength-plasticity product ≥ 20 GPa.%;
[0019] (4) High degradation uniformity: after 60 days of immersion, the corrosion pit size (i.e., equivalent diameter) is ≤12 μm, the standard deviation is ≤2 μm, and the uniformity coefficient of the corrosion pit distribution is ≥85%. The uniformity coefficient η is calculated as follows:
[0020]
[0021] Among them, p i is the number of corrosion pits in the i-th grid, is the average number of corrosion pits, and N is the number of grids.
[0022] The present invention is achieved through the following technical solutions:
[0023] The first aspect of the present invention is to provide a medical degradable Zn-Mn-Ga zinc alloy.
[0024] The Zn-Mn-Ga zinc alloy includes zinc, manganese and gallium; based on the total weight of the Zn-Mn-Ga zinc alloy being 100% (using mass fraction wt.%), the zinc content is 60 to 99.98 wt.%, preferably the manganese content is 0.01 to 20 wt.%, and preferably the gallium content is 0.01 to 20 wt.%.
[0025] The Zn-Mn-Ga zinc alloy forms the following microstructure characteristics by controlling the amount of element addition and combining bottom cycle liquid cooling casting and deformation heat treatment process:
[0026] (1) Second phase particles such as Ga2MnZn7, GaMnZn8, and (Ga,Mn)Zn9 are formed. This phase is first proposed in this patent. The size of this phase is submicron, with a volume fraction of ≤30% and an average size of ≤500nm (i.e., submicron).
[0027] (2) The Zn-Mn-Ga zinc alloy has a high degree of microstructure refinement and recrystallization, with a Zn grain size of ≤1.5 μm and a Zn grain recrystallization ratio of >95%, which significantly improves the plasticity and degradation uniformity of the alloy.
[0028] The degradation of Ga2MnZn7, GaMnZn8 and (Ga, Mn)Zn9 second phase particles in the Zn-Mn-Ga zinc alloy releases Ga with antibacterial effect. 3+ , effectively weakening the Zn 2+ The cytotoxicity and tissue inflammation produced by the large-scale release significantly improved the antibacterial properties of the alloy.
[0029] In the Zn-Mn-Ga zinc alloy, Ga 3+ and Zn 2+ The synergistic release of IL-6 significantly enhances the proliferation and migration efficiency of endothelial cells, while selectively inhibiting the excessive proliferation of smooth muscle cells.
[0030] In the Zn-Mn-Ga zinc alloy, Ga 3+ and Zn 2+ The synergistic release of MAPKs significantly increased the release of anti-inflammatory factors (such as interleukin-4) in rats, significantly promoted the polarization of macrophages to M2 anti-inflammatory and repair type, and improved the efficiency of collagen deposition in the wound.
[0031] The submicron-sized Ga2MnZn7, GaMnZn8 and (Ga, Mn)Zn9 second phase particles in the Zn-Mn-Ga zinc alloy have the following four functions:
[0032] (1) It helps to promote the nucleation of recrystallized Zn grains, relieve stress concentration during plastic deformation of Zn-Mn-Ga zinc alloy, and significantly improve its plasticity.
[0033] (2) The second phase particles of Ga2MnZn7, GaMnZn8 and (Ga,Mn)Zn9 are dispersed, which strengthens the alloy matrix, inhibits the growth of recrystallized grains, and achieves fine grain strengthening.
[0034] (3) The second phase particles of Ga2MnZn7, GaMnZn8 and (Ga,Mn)Zn9 effectively hinder dislocation movement and Zn grain boundary migration, significantly improving the strength of Zn-Mn-Ga zinc alloy and maintaining good mechanical property stability;
[0035] (4) The second phase particles of Ga2MnZn7, GaMnZn8 and (Ga,Mn)Zn9 are dispersed, forming high-density, approximately equidistant micro-galvanic pairs, avoiding the formation of local large cathode / anode areas and promoting the uniform expansion of the degradation reaction.
[0036] Preferably,
[0037] The Zn-Mn-Ga zinc alloy further includes at least one of the A group elements, the B group elements or the C group elements;
[0038] The melting point T of the A group element m >1000℃, preferably including at least one of Mo, Zr, Fe, Cu, Pm, with an addition amount of 0.01-2wt.%;
[0039] The melting point of the B group element is 600℃≤T m≤1000℃, preferably including at least one of Ag, La, Ca, Sr, Mg, with an addition amount of 0.01-2wt.%;
[0040] The C group elements include Li, which is added in an amount of 0.01 to 1 wt.%.
[0041] The effects of the above elements are as follows: (1) Group A and Group B elements can enhance the stability of Zn grain boundaries and inhibit the coarsening of Zn grains, thereby improving the strength and plasticity of Zn-Mn-Ga zinc alloys; (2) Cu can catalyze the reduction of nitrite or decompose S-nitrosothiol to promote the release of NO; (3) Ca, Sr, and Mg can enhance the osteogenic effect of Zn-Mn-Ga zinc alloys; (4) Cu, Ag, Mo, Fe, Mg, Sr, Ca, and La can synergistically improve the antibacterial properties of Zn-Mn-Ga zinc alloys; (5) Zr can reduce the thermal cracking tendency of the material and improve the rolling or extrusion forming ability of Zn-Mn-Ga zinc alloys; (6) Zr, La, and Li promote the formation of a denser oxide film, reduce microscopic galvanic corrosion, and improve the degradation uniformity of Zn-Mn-Ga zinc alloys; (7) Fe and Mg can synergistically improve the angiogenesis ability and endothelialization efficiency of Zn-Mn-Ga zinc alloys.
[0042] The antibacterial rate of the Zn-Mn-Ga zinc alloy of the present invention against Staphylococcus aureus is ≥88%, the antibacterial rate against Escherichia coli is ≥90%, the antibacterial rate against Pseudomonas aeruginosa is ≥85%, and the diameter of the inhibition zone is ≥12.5 mm;
[0043] The cell compatibility of the Zn-Mn-Ga zinc alloy of the present invention to cells such as fibroblasts, osteoblasts, smooth muscle cells and endothelial cells is ≥88%, and the cytotoxicity is level 0;
[0044] The Zn-Mn-Ga zinc alloy of the present invention has no significant effect on the migration of smooth muscle cells, but promotes the proliferation and migration of endothelial cells;
[0045] The hemolysis rate of the Zn-Mn-Ga zinc alloy of the present invention is ≤2%, and it has the properties of anti-platelet adhesion and anti-platelet activation;
[0046] The Zn in the degradation product of the Zn-Mn-Ga zinc alloy of the present invention 2+ and Ga 3+ Ions significantly enhance the release of anti-inflammatory factors such as interleukin-4, build an anti-inflammatory microenvironment, significantly improve the deposition efficiency of collagen in the wound area, and achieve structural remodeling of wound tissue.
[0047] The preparation method of the degradable Zn-Mn-Ga zinc alloy of the present invention;
[0048] The preparation method of the Zn-Mn-Ga zinc alloy includes bottom cycle liquid cooling casting and thermomechanical treatment:
[0049] The bottom cycle liquid cooling casting and thermomechanical treatment process can fully refine the second phase of the Zn-Mn-Ga zinc alloy and promote the formation of submicron-sized Ga2MnZn7, GaMnZn8 and (Ga, Mn)Zn9 second phase particles;
[0050] (1) Bottom circulation liquid cooling casting: The bottom circulation liquid cooling casting uses high-purity metals with a purity of more than 99.9% corresponding to each element in the Zn-Mn-Ga zinc alloy as raw materials, weighs the raw materials according to mass percentage and cuts them into small pieces; under vacuum or inert gas protection, the prepared raw materials are placed in a crucible in descending order of melting point and smelted, the smelting temperature is controlled at 500-800°C, and the heat is maintained for 2-15 minutes to make the raw materials become molten liquid; the high-temperature metal molten liquid is poured into a casting mold, the bottom plate of the mold is made of pure copper or other materials with high thermal conductivity, and the wall plate of the mold is made of alumina or other materials with low thermal conductivity, and a circulating liquid cooling channel is embedded in the bottom plate to achieve directional rapid cooling from top to bottom to obtain a Zn-Mn-Ga zinc alloy ingot with a strong {0001} basal plane texture; the entire cooling process takes no more than 30 seconds.
[0051] The smelting conditions are as follows: the alloy is smelted in a ceramic crucible such as Al2O3 with a melting point higher than 2000°C. The principle of selecting the crucible material is to use a ceramic material with a melting point at least 800°C higher than that of pure zinc, so as to avoid chemical contamination of the alloy of the present invention by the crucible material;
[0052] Electromagnetic stirring is applied during the smelting process, wherein the frequency of electromagnetic stirring is 1000-5000 Hz, which is conducive to the infiltration of low-melting-point metal into the melt, increases the probability of atomic contact, shortens the reaction time for forming the second phase of the alloy, and reduces the loss of unmelted or residual metal;
[0053] A melt covering agent is also added during the smelting process. Preferably, the melt covering agent is selected from at least one of KCl, NaCl, MgCl2, LiCl, rosin, and borax.
[0054] Furthermore, the material of the low thermal conductivity casting mold can be selected from materials with low thermal conductivity such as alumina and silicon nitride, and the diameter of the casting mold is 20 to 80 mm;
[0055] Furthermore, the high thermal conductivity base plate can be made of high thermal conductivity materials such as pure copper, high thermal conductivity copper alloy, high thermal conductivity aluminum alloy, etc. To further enhance the thermal conductivity effect, the base plate is embedded with a circulating liquid cooling channel;
[0056] Furthermore, the cooling medium in the circulating liquid cooling channel embedded in the base plate can be water, sodium chloride solution, calcium chloride solution, ethylene glycol aqueous solution, propylene glycol aqueous solution, or liquid nitrogen.
[0057] (2) Deformation heat treatment: The deformation heat treatment method includes at least one of the following two methods:
[0058] (i) homogenization heat treatment followed by plastic deformation;
[0059] (ii) Homogenization heat treatment is performed first, followed by solution heat treatment, and finally plastic deformation.
[0060] Preferably,
[0061] The homogenization heat treatment temperature is 150-295° C., and the temperature is kept for 1-5 hours (hereinafter, h represents hours);
[0062] The temperature of the solution heat treatment is 300-350° C., and the temperature is kept at 10-30 minutes (hereinafter referred to as “min”);
[0063] The heat treatment method is beneficial to improving the alloy performance, but too high a temperature or too long a holding time can easily lead to significant coarsening of Zn grains in the Zn-Mn-Ga zinc alloy, reduce plastic processing performance, and cause processing defects such as surface cracking.
[0064] The plastic deformation is performed by at least one of extrusion, rolling, forging, drawing or equal channel angular extrusion;
[0065] The temperature of the plastic deformation is 20 to 350°C;
[0066] During the extrusion, the corresponding extrusion ratio is 8 to 80, and the extrusion speed is 0.01 to 8 mm·s -1 ;
[0067] During the rolling, the deformation of a single rolling pass is 2% to 30%, the number of rolling passes is 1 to 15, and the rolling speed is 0.1 to 0.8 m·s -1 .
[0068] The forging method is at least one of free forging, die forging or rotary forging, and the forging rate is 200 to 500 m·s -1 .
[0069] During the drawing, the wire is annealed at 250-350° C. for 1 minute after each drawing process, and the deformation amount of each process is a diameter reduction of 0.5-1.0 mm, until a wire with a diameter of 1.0-2.5 mm is obtained.
[0070] During the equal channel angular extrusion, the corresponding extrusion passes are 2 to 18, and the extrusion speed is 0.01 to 10 mm·s -1, the extrusion path is at least one of the A path, C path, BA path, and BC path.
[0071] Among them, path A is the process in which the billet enters the next extrusion process directly without rotation after the first extrusion;
[0072] The C path is a process in which the billet rotates 180° after each extrusion to enter the next extrusion process;
[0073] The BA path is that after the billet is extruded for the first time, the billet is rotated 90° for the second time, rotated 90° in the opposite direction before the third extrusion, and rotated 90° in the opposite direction for the fourth time, and so on;
[0074] The BC path is a process in which the billet rotates 90° in the same direction after each extrusion to enter the next extrusion process.
[0075] The plastic deformation can refine the micron-sized (ie ≥5μm) Ga2MnZn7, GaMnZn8 and (Ga,Mn)Zn9 second phase particles in the cast Zn-Mn-Ga zinc alloy structure to submicron-sized (ie ≤500nm) and disperse them in the matrix.
[0076] The bottom-cycle liquid-cooled casting and thermomechanical heat treatment process precipitates a large number of submicron-sized Ga2MnZn7, GaMnZn8, and (Ga, Mn)Zn9 second-phase particles in the Zn-Mn-Ga zinc alloy. The bottom-cycle liquid-cooled casting allows the alloying elements Mn and Ga to dissolve as much as possible into the alloy matrix. The thermomechanical heat treatment then guides the precipitation of the submicron-sized Ga2MnZn7, GaMnZn8, and (Ga, Mn)Zn9 second-phase particles, providing a large amount of deformation energy and nucleation sites. If the temperature and time of the thermomechanical heat treatment exceed the specified range of the present invention, the number of submicron-sized Ga2MnZn7, GaMnZn8, and (Ga, Mn)Zn9 second-phase particles will be significantly reduced or the size of these phases will be abnormally coarse, thereby reducing the various properties of the Zn-Mn-Ga zinc alloy.
[0077] The present invention provides the application of a degradable Zn-Mn-Ga zinc alloy for high-performance vascular stents:
[0078] The Zn-Mn-Ga zinc alloy of the present invention is suitable for preparing medical implants such as degradable coronary stents and vascular stents; it can also be used to prepare soluble bridge plugs, soluble ball seats, soluble fracturing balls, soluble oil pipes, alloy die-castings such as bearings, molds, plate and shell parts, wear-resistant and shock-absorbing parts, hot-dip galvanized materials, electrogalvanized materials, mechanical galvanized materials, construction zinc materials, battery zinc materials, printing zinc materials, zinc-based alloy solders, etc. for oil drills.
[0079] Compared with the prior art, the present invention has at least the following characteristics and advantages:
[0080] 1. The plasticity and strength of the Zn-Mn-Ga zinc alloy of the present invention are significantly higher than those of pure zinc: elongation ≥90%, yield strength ≥250 MPa, tensile strength ≥280 MPa, hardness ≥65 HV, and tensile strength ≥580 MPa.
[0081] 2. The bottom cycle liquid cooling casting and deformation heat treatment process provided by the present invention promotes the formation of a large number of submicron Ga2MnZn7, GaMnZn8 and (Ga, Mn)Zn9 second phase particles. These three phases are discovered for the first time in the present invention.
[0082] 4. The submicron-sized Ga2MnZn7, GaMnZn8 and (Ga, Mn)Zn9 second phases formed by the Zn-Mn-Ga zinc alloy of the present invention significantly improve the plasticity of the Zn-Mn-Ga zinc alloy; at the same time, the degradation uniformity is significantly improved, the cytotoxicity of the metabolites of the alloy elements is significantly reduced, and the requirements for biocompatibility optimization are met.
[0083] 5. The zinc grain structure of the Zn-Mn-Ga zinc alloy of the present invention is highly refined, the Zn grain size is ≤1.5μm, the volume fraction of the second phases of Ga2MnZn7, GaMnZn8 and (Ga,Mn)Zn9 is ≤30%, and the size of these second phase particles (i.e., equivalent diameter) is ≤500nm.
[0084] 6. The Zn-Mn-Ga zinc alloy of the present invention has good biological activity, with a cell compatibility of ≥88% for cells such as fibroblasts, osteoblasts, smooth muscle cells and endothelial cells, and a cytotoxicity of level 0; an antibacterial rate against Staphylococcus aureus of ≥88%, an antibacterial rate against Escherichia coli of ≥90%, and an antibacterial rate against Pseudomonas aeruginosa of ≥85%, with an inhibition zone diameter of ≥12.5 mm; a hemolysis rate of ≤2%, and has anti-platelet adhesion and anti-platelet activation properties; it significantly improves the deposition efficiency of collagen in the wound area, achieving structural remodeling of wound tissue.
[0085] 7. The preparation method provided by the present invention is easy to realize industrial batch production. BRIEF DESCRIPTION OF THE DRAWINGS
[0086] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0087] Figure 1This is a scanning electron microscope photograph of submicron-sized Ga2MnZn7, GaMnZn8 and (Ga,Mn)Zn9 second phase particles in Zn-Mn-Ga zinc alloy.
[0088] Figure 2 The figure shows the compatibility test results of cells in 45% Zn-Mn-Ga zinc alloy extract.
[0089] Figure 3 This is the inhibition zone of bacteria growth caused by ions released during the degradation of Zn-Mn-Ga zinc alloy.
[0090] Figure 4 This is the morphology of platelets adhered to the surface of Zn-Mn-Ga zinc alloy after incubation with blood for 1 hour. DETAILED DESCRIPTION
[0091] The present invention will be further described below with reference to the following examples, which are provided for illustrative purposes only and are not intended to limit the present invention.
[0092] Test method:
[0093] The room temperature tensile mechanical properties, room temperature bending properties, antibacterial properties and biocompatibility tests of Zn-Mn-Ga zinc alloy were carried out.
[0094] Evaluate room temperature tensile mechanical properties according to GB / T 228.1-2010 "Tensile tests on metallic materials - Part 1: Room temperature test methods";
[0095] The room temperature bending properties were evaluated according to GB / T 1449.5-2005 “Metallic materials - Tensile tests Part 5: Three-point bending test method at room temperature”;
[0096] Evaluate in vitro cytocompatibility according to GB / T 16886.5-2022 "Biological evaluation of medical devices - Part 5: In vitro cytotoxicity tests";
[0097] Evaluate in vitro blood compatibility according to GB / T 16886.4-2022 “Biological evaluation of medical devices – Part 4: Selection of tests for interactions with blood”;
[0098] Evaluate in vivo biocompatibility according to GB / T 16886.6-2022 "Biological evaluation of medical devices Part 6: Local reaction test after implantation"
[0099] The percentages used in the following examples are by mass unless otherwise specified.
[0100] Example 1:
[0101] Composition, preparation and performance testing of medical biodegradable Zn-Mn-Ga ternary alloys.
[0102] The chemical compositions of the 15 inventive examples of the medical degradable Zn-Mn-Ga based ternary alloy components are shown in Table 1-1.
[0103] The preparation and processing method of the medical degradable Zn-Mn-Ga series ternary alloy includes bottom cycle liquid cooling casting and deformation heat treatment process.
[0104] The ingredients are prepared according to the ingredients of Invention Example 1-15 shown in Table 1-1, and the raw materials are weighed according to mass percentage and cut into small pieces. Among them, the raw materials Zn, Mn, and Ga are high-purity metals with a purity greater than 99.99%. They are smelted in a crucible under argon protection, and the smelting temperature is controlled at 550°C. The smelting temperature is kept for 5 minutes to make the raw materials into molten liquid; the high-temperature molten metal liquid is poured into a casting mold, the bottom plate of the mold is a pure copper material with high thermal conductivity, and the wall plate of the mold is a silicon nitride material with low thermal conductivity. The diameter of the casting mold is 25 mm; a Zn-Mn-Ga zinc alloy ingot with a strong {0001} basal plane texture is obtained by directional rapid cooling from top to bottom with circulating liquid nitrogen embedded in the bottom plate; the metal liquid is cooled from 550°C to 25°C, and the entire cooling process takes 10 to 15 seconds.
[0105] The alloy is smelted in a ceramic crucible such as Al2O3 with a melting point higher than 2000°C. The principle of selecting the crucible material is to use a ceramic material with a melting point at least 800°C higher than that of pure zinc, so as to avoid chemical contamination of the alloy of the present invention by the crucible material;
[0106] Electromagnetic stirring is applied during the melting process, with a frequency of 1000 Hz. This facilitates the infiltration of the low-melting-point metal into the melt, increases the probability of atomic contact, shortens the reaction time for the formation of Ga2MnZn7, GaMnZn8, and (Ga,Mn)Zn9 second phases, and reduces the loss of unmelted or residual metal.
[0107] During the smelting process, NaCl melt covering agent is added, which is beneficial to reduce metal oxidation and the formation of impurities and improve the purity of the Zn-Mn-Ga series ternary alloy ingot.
[0108] The temperature of the homogenization heat treatment is 150℃, which is kept for 1 hour and then cooled in the furnace; the temperature of the solution heat treatment is 300℃, which is kept for 10 minutes and then cooled in the furnace.
[0109] Rolling speed is 0.2m·s -1The deformation of a single pass was 20% to 25%, and the total deformation was 98%. Since the inventive alloy 1-15 in Table 1-1 has good formability, no annealing was required between rolling passes. The surface quality of the finally obtained rolled wire was good, and no cracks appeared on the surface. In comparison, cracks appeared on the surface of the Zn-0.4Li and Zn-0.8Li alloy wires prepared by the same method.
[0110] The structure of the Zn-Mn-Ga ternary alloy of Invention Example 1-15 in Table 1-1 was observed by electron backscatter diffraction (EBSD), and it was found that the average size of the Zn grains was ≤1.4μm, and the size of the second phase particles (i.e., the equivalent diameter) was ≤500nm.
[0111] The room-temperature tensile properties of the Zn-Mn-Ga ternary alloy of Inventive Example 1-15 in Table 1-1 were measured to be: yield strength 230-312 MPa, tensile strength 320-395 MPa, and elongation 91%-193%. The room-temperature tensile properties of the pure zinc alloy of the comparative example, prepared using the same method, were: yield strength 30-50 MPa, tensile strength 80-120 MPa, and elongation 5%-35%. This indicates that the submicron-sized Ga2MnZn7, GaMnZn8, and (Ga,Mn)Zn9 secondary phases in the Zn-Mn-Ga ternary alloy of Inventive Example 1-15 significantly improve the material's room-temperature mechanical properties.
[0112] The flexural strength of the Zn-Mn-Ga ternary alloy of invention example 1-15 in Table 1-1 was measured to be 570-700 MPa, while the flexural strength of the comparative examples of pure zinc, Zn-1Mn, Zn-1Cu, Zn-0.6Fe, Zn-0.6Ca, etc. prepared by the same method was <550 MPa.
[0113] It was measured that the cell compatibility of the Zn-Mn-Ga system ternary alloy of invention example 1-15 in Table 1-1 for cells such as fibroblasts, osteoblasts, smooth muscle cells and endothelial cells is ≥90%, and the cytotoxicity is level 0; the antibacterial rate against Staphylococcus aureus is ≥90%, the antibacterial rate against Escherichia coli is ≥95%, the antibacterial rate against Pseudomonas aeruginosa is ≥89%, and the inhibition zone diameter is ≥14.5 mm.
[0114] The hemolysis rate of the Zn-Mn-Ga ternary alloy of invention example 1-15 in Table 1-1 was measured to be ≤2%, and it has the properties of anti-platelet adhesion and anti-platelet activation; it promotes the release of anti-inflammatory factors such as interleukin-4, constructs an anti-inflammatory microenvironment, significantly improves the deposition efficiency of collagen in the wound area, and realizes the structural remodeling of the wound tissue.
[0115] The properties of some inventive examples of Zn-Mn-Ga ternary alloys and comparative examples are shown in Table 1-2.
[0116] Table 1-1
[0117]
[0118]
[0119] Table 1-2
[0120]
[0121] Example 2:
[0122] Composition, preparation and performance testing of medical biodegradable Zn-Mn-Ga quaternary alloys.
[0123] The chemical compositions of the 33 inventive examples of the medical degradable Zn-Mn-Ga quaternary alloy components are shown in Table 2-1.
[0124] The preparation and processing method of the medical degradable Zn-Mn-Ga series quaternary alloy comprises bottom cycle liquid cooling casting and deformation heat treatment processes.
[0125] The ingredients were prepared according to the ingredients of Invention Examples 16-48 shown in Table 2-1, and the raw materials were weighed according to mass percentage and cut into small pieces. The raw materials Zn, Mn, and Ga were high-purity metals with a purity greater than 99.99%. They were smelted in a crucible under argon protection, and the smelting temperature was controlled at 650°C. The smelting temperature was kept at 10 minutes to make the raw materials molten liquid. The high-temperature molten metal liquid was poured into a casting mold. The bottom plate of the mold was a pure copper material with high thermal conductivity, and the wall plate of the mold was an alumina material with low thermal conductivity. The diameter of the casting mold was 50 mm. The bottom plate was embedded with circulating water and directional rapid cooling from top to bottom was used to obtain a Zn-Mn-Ga zinc alloy ingot with a strong {0001} basal plane texture. The molten metal was cooled from 650°C to 25°C, and the entire cooling process took 15 to 20 seconds.
[0126] The alloy is smelted in a ceramic crucible such as Al2O3 with a melting point higher than 2000°C. The principle of selecting the crucible material is to use a ceramic material with a melting point at least 800°C higher than that of pure zinc, so as to avoid chemical contamination of the alloy of the present invention by the crucible material;
[0127] Electromagnetic stirring is applied during the melting process, where the frequency of electromagnetic stirring is 3000 Hz. This is conducive to the infiltration of low-melting-point metals into the melt, increases the probability of atomic contact, shortens the reaction time for the formation of Ga2MnZn7, GaMnZn8 and (Ga,Mn)Zn9 second phases, and reduces the loss of unmelted or residual metal;
[0128] KCl melt covering agent is added during the smelting process, which is beneficial to reducing metal oxidation and the formation of impurities and improving the purity of the Zn-Mn-Ga quaternary alloy ingot.
[0129] The temperature of the homogenization heat treatment is 220°C, which is kept for 3 hours and then cooled in the furnace.
[0130] The extrusion ratio corresponding to the extrusion is 20 and the extrusion speed is 1 mm·s -1 .
[0131] The temperature of the annealing process is 130° C., the time is 3 h, the annealing device is a heating furnace, and the cooling method is water cooling.
[0132] The structure of the Zn-Mn-Ga quaternary alloy of Inventive Example 16-48 in Table 2-1 was observed by electron backscatter diffraction (EBSD), and the average size of the Zn grains was found to be ≤1.5μm, and the size of the second phase particles (ie, equivalent diameter) was ≤1μm.
[0133] The room-temperature tensile properties of the Zn-Mn-Ga quaternary alloy of Inventive Example 16-48 in Table 2-1 were measured to be: yield strength 250-320 MPa, tensile strength 300-480 MPa, and elongation 80%-196%. The room-temperature tensile properties of the pure zinc alloy of the comparative example, prepared using the same method, were: yield strength 30-45 MPa, tensile strength 68-110 MPa, and elongation 5%-30%. This indicates that the submicron-sized Ga2MnZn7, GaMnZn8, and (Ga,Mn)Zn9 secondary phases in the Zn-Mn-Ga quaternary alloy of Inventive Example 16-48 significantly improve the material's room-temperature mechanical properties.
[0134] The flexural strength of the quaternary alloy of the invention example 16-48Zn-Mn-Ga system in Table 2-1 was measured to be 580~720MPa, and the flexural strength of the comparative examples of pure zinc, Zn-1Mn, Zn-1Cu, Zn-1Fe, etc. prepared by the same method was ≤570MPa.
[0135] It was measured that the cell compatibility of the Zn-Mn-Ga quaternary alloy of invention example 16-48 in Table 2-1 for cells such as fibroblasts, osteoblasts, smooth muscle cells and endothelial cells was ≥88%, and the cytotoxicity was level 0; the antibacterial rate against Staphylococcus aureus was ≥88%, the antibacterial rate against Escherichia coli was ≥90%, the antibacterial rate against Pseudomonas aeruginosa was ≥85%, and the inhibition zone diameter was ≥12.5 mm.
[0136] The hemolysis rate of the Zn-Mn-Ga quaternary alloy of invention example 16-48 in Table 2-1 was measured to be ≤2%, and it has the properties of anti-platelet adhesion and anti-platelet activation; it promotes the release of anti-inflammatory factors such as interleukin-4, constructs an anti-inflammatory microenvironment, significantly improves the deposition efficiency of collagen in the wound area, and realizes the structural remodeling of the wound tissue.
[0137] The properties of some inventive examples of Zn-Mn-Ga quaternary alloys and comparative examples are shown in Table 2-2.
[0138] Table 2-1
[0139]
[0140]
[0141] Table 2-2
[0142]
[0143] Example 3:
[0144] Composition, preparation and performance testing of medical biodegradable Zn-Mn-Ga quinary alloys.
[0145] The chemical compositions of the 30 inventive examples of the medical degradable Zn-Mn-Ga based quinary alloy components are shown in Table 3-1.
[0146] The preparation and processing method of the medical degradable Zn-Mn-Ga series five-element alloy comprises bottom-circulation liquid cooling casting and deformation heat treatment processes.
[0147] The ingredients were prepared according to the ingredients of Invention Examples 49-79 shown in Table 3-1, and the raw materials were weighed according to mass percentage and cut into small pieces. The raw materials Zn, Mn, and Ga were high-purity metals with a purity greater than 99.99%. They were smelted in a crucible under argon protection, and the smelting temperature was controlled at 800°C. The smelting temperature was kept for 15 minutes to make the raw materials molten liquid. The high-temperature molten metal liquid was poured into a casting mold. The bottom plate of the mold was a pure copper material with high thermal conductivity, and the wall plate of the mold was an alumina material with low thermal conductivity. The diameter of the casting mold was 80 mm. The bottom plate was embedded with circulating liquid nitrogen and directional rapid cooling was carried out from top to bottom to obtain a Zn-Mn-Ga zinc alloy ingot with a strong {0001} basal plane texture. The metal liquid was cooled from 800°C to 25°C, and the entire cooling process took 20 to 25 seconds.
[0148] The alloy is smelted in a ceramic crucible such as Al2O3 with a melting point higher than 2000°C. The principle of selecting the crucible material is to use a ceramic material with a melting point at least 800°C higher than that of pure zinc, so as to avoid chemical contamination of the alloy of the present invention by the crucible material;
[0149] Electromagnetic stirring is applied during the melting process, with a frequency of 5000 Hz. This facilitates the infiltration of the melt by the low-melting-point metal, increases the probability of atomic contact, shortens the reaction time for the formation of Ga2MnZn7, GaMnZn8, and (Ga,Mn)Zn9 second phases, and reduces the loss of unmelted or residual metal.
[0150] MgCl2 melt covering agent is added during the smelting process, which is beneficial to reduce metal oxidation and the formation of impurities and improve the purity of the Zn-Mn-Ga series quinary alloy ingot.
[0151] The homogenization heat treatment temperature is 290°C, which is kept for 5 hours and then cooled in the furnace.
[0152] The wire was annealed at 300°C for 1 minute after each drawing pass, with a 1.0 mm diameter reduction per pass, until a wire with a diameter of 2.5 mm was obtained. The resulting drawn wire had a good surface quality and was free of cracks. In comparison, Zn-0.4Fe and Zn-0.8Fe alloy wires prepared using the same method exhibited surface cracks.
[0153] The structure of the Zn-Mn-Ga quinary alloy of invention example 49-79 in Table 3-1 was observed by electron backscatter diffraction (EBSD), and the average size of the Zn grains was measured to be ≤1.3μm, and the size of the second phase particles (ie, equivalent diameter) was ≤450nm.
[0154] The room-temperature tensile properties of the Zn-Mn-Ga quinary alloy of Inventive Example 49-79 in Table 3-1 were measured to be: yield strength 260-395 MPa, tensile strength 320-485 MPa, and elongation 91%-193%. The room-temperature tensile properties of the pure zinc alloy of the comparative example, prepared using the same method, were: yield strength 275-365 MPa, tensile strength 332-472 MPa, and elongation 80%-196%. This indicates that the submicron-sized Ga2MnZn7, GaMnZn8, and (Ga,Mn)Zn9 secondary phases in the Zn-Mn-Ga quinary alloy of Inventive Example 49-79 significantly improve the material's room-temperature mechanical properties.
[0155] The flexural strength of the inventive example 49-79Zn-Mn-Ga five-element alloy in Table 3-1 was measured to be 570~700MPa, and the flexural strength of the comparative example pure zinc, Zn-1Li, Zn-1Sr, Zn-0.6Mg, Zn-0.6Ca alloys prepared by the same method was ≤560MPa.
[0156] It was measured that the cell compatibility of the Zn-Mn-Ga based five-element alloy of invention example 49-79 in Table 3-1 for cells such as fibroblasts, osteoblasts, smooth muscle cells and endothelial cells was ≥85%, and the cytotoxicity was level 0; the antibacterial rate against Staphylococcus aureus was ≥88%, the antibacterial rate against Escherichia coli was ≥93%, the antibacterial rate against Pseudomonas aeruginosa was ≥87%, and the inhibition zone diameter was ≥12.5 mm.
[0157] The hemolysis rate of the Zn-Mn-Ga five-element alloy of invention example 49-79 in Table 3-1 was measured to be ≤2%, and it has the properties of anti-platelet adhesion and anti-platelet activation; it promotes the release of anti-inflammatory factors such as interleukin-4, constructs an anti-inflammatory microenvironment, significantly improves the deposition efficiency of collagen in the wound area, and realizes the structural remodeling of the wound tissue.
[0158] The properties of some inventive examples of Zn-Mn-Ga quinary alloys and comparative examples are shown in Table 3-2.
[0159] Table 3-1
[0160]
[0161]
[0162] Table 3-2
[0163]
Claims
1. A multifunctional, highly plastic, degradable Zn-Mn-Ga zinc alloy, characterized in that: The composition of the Zn-Mn-Ga zinc alloy is as follows: the content of zinc is 60-99.98 wt.%, the content of manganese is 0.01-20 wt.%, and the content of gallium is preferably 0.01-20 wt.%; 2+ Release rate ≥1.0mg / (cm 2 ·day), Mn 2+ Release rate ≥0.05mg / (cm 2 ·day), Ga 3+ Release rate ≥0.1mg / (cm 2 ·day), the cytotoxicity of alloy element metabolic ions is level 0, the antibacterial rate is ≥85%, the release of rat anti-inflammatory factor interleukin-4 is significantly promoted, with an increase of ≥100%, and the efficiency of collagen deposition in the wound is improved, with an increase of ≥50%; the yield strength of the Zn-Mn-Ga zinc alloy is ≥250MPa, the tensile strength is ≥280MPa, the hardness is ≥65HV, the tensile strength is ≥580MPa, the elongation is ≥90%, the stress concentration factor is ≤1.6, and the strength and plasticity product is ≥20GPa.%; the degradation uniformity of the Zn-Mn-Ga zinc alloy is high. After immersion for 60 days, the equivalent diameter of the corrosion pit size is ≤12μm, the standard deviation is ≤2μm, and the uniformity coefficient of the corrosion pit distribution is ≥85%.
2. A multifunctional, highly plastic, degradable Zn-Mn-Ga zinc alloy according to claim 1, characterized in that: The medical degradable Zn-Mn-Ga zinc alloy with both high functionality and high plasticity further comprises at least one of the elements of group A, group B or group C; The melting point T of the A group element m >1000℃, including at least one of Mo, Zr, Fe, Cu, Pm, added in an amount of 0.01-2wt.%; The melting point of the B group element is 600℃≤T m ≤1000℃, including at least one of Ag, La, Ca, Sr, Mg, with the addition amount being 0.01-2wt.%; The C group elements include Li, which is added in an amount of 0.01 to 1 wt.%.
3. A multifunctional, highly plastic, degradable Zn-Mn-Ga zinc alloy according to claim 1 or 2, characterized in that: The volume fraction of Ga2MnZn7, GaMnZn8 and (Ga,Mn)Zn9 second phase particles in the medical biodegradable Zn-Mn-Ga zinc alloy with both high functionality and high plasticity is ≤30%, and the average size is ≤500nm; the Zn-Mn-Ga zinc alloy has a high degree of microstructure refinement and recrystallization, the Zn grain size is ≤1.5μm, and the Zn grain recrystallization ratio is >95%.
4. A method for preparing the multifunctional, highly plastic, degradable Zn-Mn-Ga zinc alloy according to any one of claims 1 to 3, characterized in that: Adopt bottom cycle liquid cooling casting and deformation heat treatment process: (1) Bottom circulation liquid cooling casting: The bottom circulation liquid cooling casting process is to use high-purity metals with a purity of more than 99.9% corresponding to each element in the Zn-Mn-Ga zinc alloy as raw materials, weigh the raw materials according to mass percentage and cut them into small pieces; under vacuum or inert gas protection, put the prepared raw materials into a crucible in descending order of melting point and melt them, and control the melting temperature at 500-800°C. The materials are kept warm for 2-15 minutes to make the raw materials into molten metal liquid; the molten metal liquid is poured into a casting mold, the bottom plate of the mold is made of a material with high thermal conductivity, and the wall plate of the mold is made of an alumina material with low thermal conductivity. The bottom plate is embedded with a circulating liquid cooling channel to achieve directional cooling from top to bottom, and a Zn-Mn-Ga zinc alloy ingot with a strong {0001} basal plane texture is obtained; the entire cooling process takes no more than 30 seconds; (2) Deformation heat treatment: The deformation heat treatment method includes at least one of the following two methods: 1) Homogenization heat treatment is performed first, followed by plastic deformation; 2) First perform homogenization heat treatment, then perform solution heat treatment, and finally perform plastic deformation.
5. The method for preparing a multifunctional, highly plastic degradable Zn-Mn-Ga zinc alloy according to claim 4, characterized in that: The material of the casting mold described in step (1) is selected from alumina and silicon nitride, which have low thermal conductivity. The diameter of the casting mold is 20 to 80 mm. The high thermal conductivity material used for the mold floor is pure copper, high thermal conductivity copper alloy, or high thermal conductivity aluminum alloy. The bottom plate is embedded with a circulating liquid cooling channel, and the cooling medium in the circulating liquid cooling channel embedded in the bottom plate is water, sodium chloride solution, calcium chloride solution, ethylene glycol aqueous solution, propylene glycol aqueous solution or liquid nitrogen.
6. The method for preparing the multifunctional, highly plastic degradable Zn-Mn-Ga zinc alloy according to claim 4, characterized in that: In step (1), electromagnetic stirring is applied during the smelting process, and the frequency of the electromagnetic stirring is 1000 to 5000 Hz. A melt covering agent is also added during the smelting process, and the melt covering agent is selected from at least one of KCl, NaCl, MgCl2, LiCl, rosin, and borax.
7. The method for preparing the multifunctional, highly plastic degradable Zn-Mn-Ga zinc alloy according to claim 4, characterized in that: The homogenization heat treatment temperature is 150-295°C, and the temperature is kept for 1-5 hours; The temperature of the solution heat treatment is 300-350° C., and the temperature is kept at 10-30 minutes.
8. The method for preparing a multifunctional, highly plastic degradable Zn-Mn-Ga zinc alloy according to claim 4, characterized in that: In step (2), the plastic deformation is performed by at least one of extrusion, rolling, forging, drawing or equal channel angular extrusion, and the temperature of the plastic deformation is 20 to 350°C.
9. The method for preparing the multifunctional, highly plastic degradable Zn-Mn-Ga zinc alloy according to claim 8, characterized in that: During extrusion, the corresponding extrusion ratio is 8 to 80, and the extrusion speed is 0.01 to 8 mm·s -1 ; During rolling, the deformation of a single pass is 2% to 30%, the number of rolling passes is 1 to 15, and the rolling speed is 0.1 to 0.8 m·s -1 ; The forging method is at least one of open forging, die forging or rotary forging, and the forging rate is 200-500 m·s -1 ; During drawing, annealing is performed at 250-350°C for 1 minute after each drawing process, and the deformation amount of each process is 0.5-1.0 mm in diameter reduction until a wire with a diameter of 1.0-2.5 mm is obtained; During equal channel angular extrusion, the corresponding extrusion passes are 2 to 18, and the extrusion speed is 0.01 to 10 mm·s -1 , the extrusion path is at least one of the A path, C path, BA path, and BC path. Among them, path A is the process in which the billet enters the next extrusion process directly without rotation after the first extrusion; The C path is a process in which the billet rotates 180° after each extrusion to enter the next extrusion process; The BA path is that after the billet is extruded for the first time, the billet is rotated 90° for the second time, rotated 90° in the opposite direction before the third extrusion, and rotated 90° in the opposite direction for the fourth time, and so on; The BC path is a process in which the billet rotates 90° in the same direction after each extrusion to enter the next extrusion process.
10. A multifunctional, highly plastic, degradable Zn-Mn-Ga zinc alloy as claimed in claims 1-3, characterized in that: The alloy is suitable for preparing degradable coronary stents and vascular stent medical implants; it can also be used to prepare soluble bridge plugs, soluble ball seats, soluble fracturing balls, soluble oil pipes, alloy die-castings such as bearings, molds, plate and shell parts, wear-resistant and shock-absorbing parts, hot-dip galvanized materials, electrogalvanized materials, mechanical galvanized materials, construction zinc materials, battery zinc materials, printing zinc materials or zinc-based alloy solders for oil drills.